7-Ethyl-10-Hydroxycamptothecin, a DNA Topoisomerase I Inhibitor, Performs BRD4 Inhibitory Activity and Inhibits Human Leukemic Cell Growth - Wang, Airong; Li, Lingling; Li, Mengya; Wang, Shujuan; Wang, Chong (Frontiers in Pharmacology, 2021)
7-Ethyl-10-hydroxycamptothecin (SN-38) is an active metabolite of CPT-11, which can inhibit DNA topoisomerase I, DNA synthesis and cause frequent DNA single-strand breaks. In our study, SN-38 was characterized as a potent and reversible BRD4 inhibitor (IC50 = 660.2 nM against BRD4(BD1) and IC50 = 547.7 nM against BRD4(BD2)) in biochemical assay using drug repurposing strategy. Additional cellular assay suggested that SN-38 can bind BRD4 in human leukemic cell K562 and inhibit cell growth with IC50 = 0.2798 μM in a BRD4 dependent manner partially. Additionally, mechanism study indicated that SN-38 can induce the accumulation of BRD4 substrate c-Myc and cleavage of caspase 3. In sum, our findings identified BRD4 as a new target of SN-38 and reveals SN-38 as a modifier of histone acetylation reader for the first time, which may provide a new insight for further optimization of dual target inhibitor.